EVALUASI KINERJA PENYULINGAN MINYAK NILAM DI KABUPATEN GAYO LUES - Emmia Tambarta; Fauzi Fauzi; Ramayana Ramayana (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2021)
This study aims to evaluate patchouli oil refining in various production areas and varieties in Gayo Lues Regency. The research method used is Latin square design based on the type of production area, patchouli variety and the distiller used. The performance of the distiller observed varied according to the area of production, patchouli varieties and specifications of the distiller. The results showed that the performance of the distiller differed according to the area of production, variety and type of distiller. This also causes variations in the performance and profits of patchouli oil refining business. The more suitable the agro-climatic production area, the smaller the investment value needed to produce good quality patchouli with high yields. For areas that do not meet the requirements for growing each variety, investment with a larger value is required. The performance of the distillation tool is getting better when varieties are cultivated that are in accordance with the growing requirements of each variety.